When risk becomes invisible in the everyday life of day care. Issue 1 (2nd January 2016) - Villumsen, Anne Marie; Kristensen, Ole Steen
Abstract : Both the identification of children at risk in day care and multidisciplinary collaboration with other professions have a political focus. This study was designed as an organizational field study and attempts to establish a coherent practice of multidisciplinary collaboration between day care and social services. This article focuses on the mono-professional pedagogical identification of children at risk as well as on the underlying process of professional reasoning. Interviews with day care staff are analysed and the findings give reason to assume that central aspects of the children at risk and their life circumstances become invisible in the everyday life of day care. Due to defensive routines as well as an organizational culture that frames and creates a non-explicitly structured practice using intuitive processes, the problems of children at risk become invisible in the everyday life of day care. When risk become invisible, it not only impedes the mono-professional help the children receive, it also inhibits a crucial multidisciplinary collaborative provision of support to children at risk and their families. The identification of children at risk seems to be based on an unexamined selection of significant information, processed by intuitive processes.